An updated lineage-based tribal classification of Apiaceae subfamily Apioideae with special focus on Iranian genera. Issue 1 (10th December 2020) - Mousavi, Sabereh; Mozaffarian, Valiollah; Mummenhoff, Klaus; Downie, Stephen R.; Zarre, Shahin
Abstract : Molecular phylogenetic studies have had major impacts on the delineation of higher-level taxa in many plant groups. Apiaceae subfamily Apioideae, its largest subfamily, is in the process of major systematic rearrangements owing to these studies. Iran, with more than one fourth of all apioid genera, is a biodiversity hotspot for this subfamily, though the sampling of these taxa from this region has been insufficient. Currently, 111 apioid genera are recognized in Iran of which 18 including five endemics are not presented or are under-represented in previous phylogenetic studies. We used the sequences of nuclear ribosomal internal transcribed spacer (ITS) and chloroplast rps16 intron ( rps16 ) regions from 325 and 149 accessions, respectively, representing most of the known genera of Apioideae from Iran. Twenty-nine ITS and 26 rps16 sequences were newly generated for this study. Phylogenetic trees were reconstructed using Bayesian inference, Maximum likelihood, and Maximum parsimony methods. The results assign the endemic genera Ergocarpon to Echinophoreae, Lomatopodium to Selineae, Froriepia and Oliveria to Pyramidoptereae, and Stenotaenia to Tordylieae. In addition, Ormosciadium, morphologically characterized by moniliform and inflated mericarp margins, is assigned to Tordylieae. Neocryptodiscus persicus is shown to be a synonym of Prangos persica . The previous placement of Heptaptera in the Physospermopsis clade is not correct and it should be moved to the Opopanax clade. Morphological characters deemed to be of high diagnostic value are the shape of leaf segments, presence of tubers, colour of petals, and mericarp features including shape, presence of lateral or dorsal wings, and type of compression and indumentum. A diagnostic key to 19 tribes, nine subtribes and other major clades compatible with these taxonomic ranks and an updated list of genera of Apioideae occurring in Iran with their tribal and subtribal position is provided.